2018
DOI: 10.1111/micc.12464
|View full text |Cite
|
Sign up to set email alerts
|

From pregnancy to cardiovascular disease: Lessons from relaxin‐deficient animals to understand relaxin actions in the vascular system

Abstract: Early maternal vascular adaptations to pregnancy are predominantly driven by changes in vascular tone, reactivity, and remodeling. Failure of the maternal systemic vasculature to adapt sufficiently can lead to serious complications of pregnancy. The hormone relaxin is widely recognized for its contribution to the essential renal and systemic hemodynamic adaptations in early pregnancy through direct actions on the maternal vasculature. Studies in relaxin gene knockout mice revealed that endogenous relaxin is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…[40][41][42][43][44] In the kidney RLX is a potent vasodilator dependent on a functional NO synthase-NO system. 45 Mechanistically, RLX dilates both the afferent and efferent arterioles, causing a significant increase in renal blood flow and a marked increase in GFR and urine flow. 40,43,44 In addition, RLX has direct effects on the renal tubules, possibily via an AT 2 R-bradykininnitric oxide (NO)-cGMP mechanism, 46,47 to inhibit sodium reabsorption, 40 which may also contribute to an increase in urine flow.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44] In the kidney RLX is a potent vasodilator dependent on a functional NO synthase-NO system. 45 Mechanistically, RLX dilates both the afferent and efferent arterioles, causing a significant increase in renal blood flow and a marked increase in GFR and urine flow. 40,43,44 In addition, RLX has direct effects on the renal tubules, possibily via an AT 2 R-bradykininnitric oxide (NO)-cGMP mechanism, 46,47 to inhibit sodium reabsorption, 40 which may also contribute to an increase in urine flow.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the hemodynamic adaptations during pregnancy may be assigned to relaxin. This polypeptide is synthetized by corpus luteum and it is mainly responsible for vascular remodeling and vasodilatation, which is predominantly achieved by the stimulation of NO system and alteration in the expression of endothelin ET 1B receptors (67). Beside aforementioned hemodynamic changes, pregnancy is also characterized by the increase in renal blood flow, glomerular filtration rate, activity of the renin angiotensin aldosterone system and enhanced activity of the sympathetic nervous system.…”
Section: Pregnancy Induced Hypertensionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that Cmpd17b administered during reperfusion in vivo reduces cardiac necrosis, inflammation, cardiac remodelling, and improves cardiac function [15]. Endothelial cells release several vasoactive factors that regulate the tone of the underlying smooth muscles cells [16][17][18]. The impact of FPR agonists on the regulation of vascular tone under physiological condition remains unclear and contradicting.…”
Section: Introductionmentioning
confidence: 99%